Shedding light on restoring respiratory function after spinal cord injury - Alilain, Warren J.; Silver, Jerry (Frontiers in Molecular Neuroscience, 2009)
Loss of respiratory function is one of the leading causes of death following spinal cord injury. Because of this, much work has been done in studying ways to restore respiratory function following SCI - including pharmacological and regeneration strategies. With the emergence of new and powerful tools from molecular neuroscience, new therapeutically relevant alternatives to these approaches have become available, including expression of light sensitive proteins called channelrhodopsins. In this article we briefly review the history of various attempts to restore breathing after C2 hemisection, and focus on our recent work using the activation of light sensitive channels to restore respiratory function after experimental spinal cord injury. We also discuss how such light induced activity can help shed light on the inner workings of the central nervous system respiratory circuitry that controls diaphragmatic function.